Utilization training of rice husk waste as alternative energy in Baros District, Serang, Indonesia - Cholis, Nur; Lukmana, M. Arifudin; Fahrudin, Fahrudin; Montreano, Donny (Community Empowerment, 2021)
Farmer groups in Baros District, Serang Regency face a problem where a rice husk waste has accumulated and there has been no effort to process it into economic value products. One solution is to use rice husk waste into briquettes. Rice husk briquettes are obtained by burning dry biomass with a little air (carbonization). The method of implementing the activities carried out was by extension and demonstration of making briquettes. This activity was able to increase the knowledge and skills of the management and members of the Baros independent farmer group in the use of rice husks as an alternative energy source in the form of briquettes.